HUBUNGAN GEJALA KLINIS DENGAN HASIL PEMERIKSAAN NON-STRUCTURAL PROTEIN (NS1) PASIEN SUSPEK DENGUE DI PUSKESMAS SUKODADI: RELATIONSHIP BETWEEN CLINICAL SYMPTOMS AND NON-STRUCTURAL PROTEIN (NS1) EXAMINATION OF DENGUE SUSPECTED PATIENTS AT SUKODADI HEALTH CENTER - Eniswatin, Ida; Herawati, Dheasy; Yusmiati, Siti Nur Husnul; Rini, Yenny Puspa (Jurnal SainHealth, 2024)
Dengue fever is an endemic arbovirus disease that often causes morbidity and mortality. Rapid and appropriate treatment of dengue fever can be done if a rapid and specific test during the acute phase of infection can be done. An examination that has been developed is the dengue non-structural antigen (NS1) examination which can detect dengue virus infection earlier. The purpose of this study was to determine the relationship between clinical signs and symptoms with NS1 examination results in patients suspected of dengue fever at the Sukodadi Health Center. The type of research is descriptive analytical with a cross-sectional approach to 86 patients at the Sukodadi Health Center, Lamongan Regency using a simple random sampling technique. Data collection was carried out on patient medical records based on the results of clinical signs and symptoms of the examination and the results of the NS1 examination. The collected data were analyzed using the Chi-Square test, with a significance level of p <0.05. The results of the study showed that most patients (72.1%) were diagnosed with suspected dengue fever, most (79.1%) had negative NS1 examination results, and the Chi-Square test results obtained x count = 8.812, and p = 0.003 (<0.05), then H0 was rejected, meaning that there was a relationship between clinical signs and symptoms with NS1 examination results in patients with suspected dengue fever. The conclusion of this study is there is a significant relationship between clinical signs and symptoms with NS1 examination results in patients with suspected dengue fever